Effectiveness of Book Closing Using Web Based Accounting Online System 2.0 to Know the Company's Financial Ratios - Aisyah, Euis Sitinur; Maimunah, Maimunah; Martono, Aris (APTISI Transactions on Management (ATM), 2017)
Financial ratios are very important in a company, because it is the most effective way to find out financial data on a company by comparing the current financial statements of the company with the previous one. To facilitate this comparison, book closure can be done. Closing the book itself is useful to determine the company's financial position before closing, by looking at the final results of the profit and loss. It is known that the process of closing the book takes a long time with extra precision. However, this has become easier by using WBAOS (Web Based Accounting Online System) 2.0, because companies are more flexible in preparing financial statements, starting from the lane balance sheet, income statement, to the periodic cash flow, where this cash flow provides relevant information regarding cash in and out of the company. Keywords: ​WBAOS, Financial Ratios and Book Closure.